Evolution of hydatidosis in Spain since 2015 to 2023 (Boletín Epidemiológico Semanal, 2024)
Introduction: hydatidosis is a zoonosis typically diagnosed late and/or incidentally, caused by the parasite Echinococcus. The notification rate in Spain has been decreasing since it was included as a notifiable disease. The aim of this work is to describe the situation and evolution of human hydatidosis in Spain since 2015, with special emphasis in the last year 2023.Method: a descriptive analysis was conducted of the cases of hydatidosis reported to the National Epidemiological Surveillance Network (RENAVE) since 2015, with a special emphasis on the year 2023. Variables such as age, sex, autonomous community of residence, and exposure were analyzed. Frequencies, percentages, notification rates were calculated, and maps were created.Results: Between 2015 and 2023, 710 indigenous cases of hydatidosis were reported, with a peak in 2015 (154 cases) and decline until 2019, followed by a slight increase in 2021. In 2023, 71 indigenous cases were reported, of which 39.4% were hospitalizated, although no deaths were recorded. In 2023, the highest notification rates were observed in Extremadura, La Rioja, and C.F. Navarra, while the lowest rates were in the Comunitat Valenciana, País Vasco, and Cataluña.Discussion: a decrese in notification followed by an uptick suggests the effectiveness of control measures but also indicates persistent challenges. The presence of imported cases and regional variability reflects socioeconomic, cultural or environmental factors that must be considered in control and prevention strategies.
Keywords: Hydatidosis; Zoonosis; Epidemiological surveillance